Dispersibility and biotransformation of oils with different properties in seawater. (January 2018) - Brakstad, Odd G.; Farooq, Umer; Ribicic, Deni; Netzer, Roman
Abstract: Dispersants are used to remove oils slicks from sea surfaces and to generate small oil-droplet dispersions, which may result in enhanced biodegradation of the oil. In this study, dispersibility and biodegradation of chemically dispersed oils with different physical-chemical properties (paraffinic, naphthenic and asphaltenic oils) were compared in natural temperate SW at 13 °C. All selected oils were chemically dispersible when well-known commercial dispersants were used. However, interfacial tension (IFT) studies of the dispersed oils showed different IFT properties of the oils at 13 °C, and also different leaching of the dispersants from oil droplet surfaces. Biodegradation studies of the chemically dispersed oils were performed in a carousel system, with initial median droplet sizes <30 μm and oil concentrations of 2.5–2.8 mg/L. During biodegradation, oil droplet concentrations were rapidly reduced, in association with the emergence of macroscopic 'flocs'. Biotransformation results showed that half-lives of semivolatile total extractable organic carbon (TEOC), single target 2- to 4-ring PAH, and 22 oil compound groups used as input data in the oil spill contingency model OSCAR, did not differ significantly between the oils (P > 0.05), while n -alkanes half-lives differed significantly (P < 0.05). Biotransformation was associated with rapid microbial growth in all oil dispersions, in association with n -alkane and PAH biotransformation. These results have implications for the predictions of biodegradation of oil slicks treated with dispersants in temperate SW. Highlights: Commercial dispersants efficiently dispersed crude oils with different properties. IFT testing showed different surfactant leaching properties for oils and dispersants tested. Biodegradation of alkanes and PAH did not differ significantly between the different oils. Biodegradation of saturate and aromatic oil compound groups were provided for an oil spill model. Oil biodegradation stimulated growth of heterotrophic and oil-degrading prokaryotes in all oils.